Expression of type 1 cannabinoid receptor gene in bipolar disorder. (December 2022) - Escelsior, Andrea; Tardito, Samuele; Sterlini, Bruno; Altosole, Tiziana; Trabucco, Alice; Marozzi, Valentina; Serafini, Gianluca; Aguglia, Andrea; Amerio, Andrea; Pereira da Silva, Beatriz; Fenoglio, Daniela; Filaci, Gilberto; et al.
Abstract: Background: The Endocannabinoid System (ECBs) may have a crucial role in bipolar disorder (BD). Previous reports have not detected abnormalities in the expression of the cannabinoid receptor gene CNR1, encoding for CB1 . However, we hypothesized that differentiating between mania and depression may uncover differences in CNR1 expression levels. Methods: We recruited 44 subjects with BD type I (BD-I), in mania (n = 22) and depression (n = 22) and 25 Healthy Controls (HC). CNR1 gene expression was analyzed using a quantitative real-time polymerase chain reaction from peripheral blood mononuclear cells. Data were analyzed using frequentist non-parametric and Bayesian approaches (generalized location-scale model based on lognormal and gamma distributions). Results: Using the frequentist non-parametric approach, the depression group had lower CNR1 expression compared to the mania group (p = 0.004). In addition, there was a negative correlation between CNR1 expression and Hamilton Depression Scale score (rho = −0.37; p = 0.007). Bayesian analyses further revealed that CNR1 expression in the mania group was higher and less variable than among HC (>95% probability), while CNR1 expression in the depression group was lower and more variable than among HC (100% probability). Limitations: Lack of participants with bipolar disorder in the euthymic phase, lack of toxicology screening and evaluation of CNR1 variants. Conclusion: CNR1 expression is higher and less variable in mania than in depression. It is highly probable that these differences also distinguish individuals in different illness phases from healthy controls. Future studies are needed to clarify the role of the endocannabinoid system in bipolar disorder. Highlights: The endocannabinoid system is involved in affective regulation. CNR1 mRNA levels were higher and less variable in subjects with mania than depression. CNR1 expression correlated negatively with the severity of depression. CNR1 levels were also different between phases of bipolar disorders and healthy controls.